MENINGKATKAN AKTIVITAS SISWA MELALUI MODEL PEMBELAJARAN NHT PADA MATERI LINGKARAN DI KELAS VIII SMP NEGERI 3 KUBU TAHUN 2016 - Cahye, Cahye (Jurnal Pendidikan Matematika dan IPA, 2017)
This research is motivated by the low activity of students in receiving lessons in the classroom. This classroom action research aims to improve mathematics learning activities in class VIII SMP Negeri 3 Kubu. The solution to low activity of students conducted by researchers through the Numbered Heads Together (NHT) of cooperative learning model. The research was conducted in three cycles to 32 students. The technique of data collecting is observation by teachers and collaborators. Student activity expressed by categories of high, medium or low, the success of NHT learning models is successful, less successful or unsuccessful. Activity criteria determined by the researchers themselves with 60% of students are actively involved. Activity in this research there are four, namely: 1). Visual activities, 60% 2). Oral activities, 90%, 3). Motor activities, 85%, 4). Writing activities, 100%. Thus the NHT learning models successfully increased student activity. Keywords: Numbered Heads Together, student activity, circle